Experimental and Numerical Investigation on Dynamic Failure and Energy Dissipation of Sandstone under Coupled Static-Dynamic Loading - Kan, Jiliang; Xiao, Kun; Zhou, Kunyou; Wang, Tong; Li, Jiazhuo; Dou, Linming (Archives of Mining Sciences, 2026)
Catastrophic failures in underground rock engineering caused by coupled static-dynamic stresses result in economic losses and safety hazards globally. Quantifying rock dynamic failure and energy dissipation under such conditions is essential for mitigating geotechnical risks. This study employed modified split Hopkinson pressure bar (SHPB) experiments to perform coupled static-dynamic compression tests on sandstone under varying loading circumstances. A novel PFC-FLAC coupling methodology was developed to simulate real-time dynamic failure evolution of rock. Compared to uniaxial impact tests, more prominent phenomena of pre-peak plastic deformation stage and post-peak strain rebound are observed in the stress-strain curves of sandstone under coupled static-dynamic compression tests. The mechanical properties of sandstone are directly influenced by both dynamic stress and static stress (axial-confining pressure). Energy serves as the fundamental driving force of rock damage, and the dissipated energy has a considerable positive correlation with rock damage. Furthermore, fractal analysis quantitatively revealed progressive failure modes: local damage transitions to axial splitting and ultimately macroscopic crushing with increasing impact pressure. Crucially, elevated axial pressure accelerates impact-induced failure, while confining pressure systematically mitigates damage intensity. Post-failure analysis identified some specimens retaining structural integrity through circular platform cores with arched fracture surfaces. The failure mode is X-type conjugated failure caused by shear failure, which was verified by numerical simulations. These findings provide critical design parameters for predicting rock bursts in deep mining excavations and evaluating tunnel stability during blasting operations.